Bridging the Gap: Strengthening Mental Health Support for Female Health Professionals in Pakistan and Türkiye - Komal Atta; Ahmad Atta; Mahnoor Atta (Journal of University College of Medicine and Dentistry)
Being a part of a demanding and high-pressure field like Medicine, healthcare workers are bound to face mental health challenges. These challenges are particularly pronounced among female healthcare providers, likely due to gender-based inequalities within the system. This paper addresses the mental health challenges faced by female physicians in Turkey and Pakistan, highlighting the impact of gender-based inequalities in the healthcare system. It proposes a framework aimed at improving mental health support for female healthcare workers, emphasizing the need for equitable access to mental health services and the implementation of workplace policies that promote peer support groups. By addressing these concerns, the paper aims to enhance the professional and personal well-being of female healthcare providers, ultimately contributing to improved healthcare delivery.